STRATEGI PENGELOLAAN KEUANGAN, PENINGKATAN KONSISTENSI PRODUKSI, DAN BRANDING DIGITAL DALAM MENINGKATKAN PENJUALAN KERUPUK KAMANG - Mazelfi, Ihsani; Ramadhani, Ratih; Adisti, Adila; Saputra, Dendi Adi; Wellyalina, Wellyalina (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
This community service program aims to address three main issues faced by the partner: production, marketing, and managerial aspects. In production, problems include poor water quality, inconsistent production, product durability in packaging, and the absence of microbiological testing. Good water quality and stable supply are essential for maintaining product quality and production efficiency. In marketing, the challenges involve unprofessional packaging, limited understanding of digital marketing, and low brand awareness. Professional packaging and digital marketing strategies can enhance product value and branding. In financial management, issues include unsystematic bookkeeping, suboptimal pricing strategies, limited understanding of cost of goods sold (COGS), lack of PIRT certification, and unregistered brand intellectual property. Proper financial recording and COGS knowledge are crucial for cash flow control and accurate pricing. The program aims to improve financial management efficiency, ensure consistent production quality, and enhance branding and digital marketing. Expected outputs include a nationally accredited journal article, intellectual property registration, media publication, and promotional video.Keywords: MSMEs; Digital Marketing; SIAPIK; Water Filter; Brand Awareness